Atomic-scale observation of spontaneous hole doping and concomitant lattice instabilities in strained nickelate films. (1st February 2022) - Lin, I C; Lee, M H; Wu, P C; Lin, S C; Chen, J W; Li, C-C; Guo, G Y; Chu, Y-H; Sankar, R; Chu, M-W
Abstract: Thin oxide films are of vast opportunities for modern electronics and can facilitate emergent phenomena by factors absent in the bulk counterparts, such as the ubiquitous epitaxial strain and interfacial charge doping. Here, we demonstrate the twisting of intended bulk-metallic phases in 10-unit-cell LaNiO3, PrNiO3, and NdNiO3 films on (001)-oriented SrTiO3 into distinct charge-lattice entangled states by epitaxial strains. Using atomically-resolved electron microscopy and spectroscopy, the interfacial electron doping into SrTiO3 in the conventional context of band alignments are discounted. Instead, spontaneously doped holes that are localized and at the order of 10 13  cm −2 are atomically unraveled across all three heterointerfaces and associated with strain mitigations by the accompanied atomic intermixing with various ionic radii. The epitaxial strains also lead to condensations of monoclinic- C 2/ c lattice instabilities, which are hidden to the bulk phase diagram. The group-theoretical analysis of characteristic transition pathways unveils the strain resurrection of the hidden C 2/ c symmetry. While this strain-induced monoclinic phase in LaNiO3 remains metallic at room temperature, those in PrNiO3 and NdNiO3 turn out to be insulating. Such strain-induced monoclinic lattice instabilities and parasitic localized holes go beyond the classical elastic deformations of films upon epitaxial strains and hint on plausible hidden orders in versatile oxide heterostructures with unexpected properties, of which the exploration is only at the infancy and full of potentials.